Hubungan Voluntary Counseling and Testing (VCT) dengan Tingkat Depresi pada Penderita HIV/AIDS: Relationship of Voluntary Counseling and Testing (VCT) with Depression Levels in HIV/AIDS Patients - Marimelda Ginting; Wesli Daeli; Bambang Suryadi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: VCT counseling is a counseling activity that provides psychological support, information and knowledge of HIV/AIDS and ensures the resolution of various problems related to HIV/AIDS, including the behavior of prisoners in each prison. Methods: This study used a cross sectional design. The number of samples is 56 prisoners or inmates who suffer from HI/AIDS. The research instrument used a questionnaire measuring instrument and statistical tests using the Chi Square test. Results: Depression of HIV/AIDS sufferers in Cipinang Jati Negara Class 1 Prison experienced depression 61% more. The bivariate results showed that there was a relationship between Voluntary Counseling and Testing (VCT) and the level of depression in HIV/AIDS sufferers in Cipinang Jati Negara Jakarta Class 1 Prison with a P-value of 0.009 and an Odds Ratio of 4.63. Discussion: There is a relationship between Voluntary Counseling and Testing (VCT) and the level of depression in HIV/AIDS sufferers at the Class 1 Cipinang Jati State Prison, East Jakarta in 2020.